PENERAPAN MODEL PEMBELAJARAN KREATIF PRODUKTIF (MPKP) UNTUK MENINGKATKAN KREATIVITAS DAN PRODUKTIVITAS BELAJAR MAHASISWA PADA MATA KULIAH PENGANTAR BISNIS - Henny Indrawati (Jurnal Pendidikan, 2014)
This study aims to improve student learning creativity andproductivity through the application of Creative Productive Learning Model in theIntroductory Business class. The experiment was conducted at EconomicEducation Program, the Faculty of Teacher Education University of Riau. Thesubjects were students of the first semester of Economic Education ProgramUniversity of Riau who follow classes in Introductory Business in AcademicSemester 2013/2014. The number of students 35 people, consisting of 27 (77percent) female students, and 8 (23 percent) male students. The experiment wasconducted in three cycles; each cycle includes the stages of planning,implementation, observation and reflection. The results found that byimplementing Creative Productive Learning Model, it can increase the creativityand productivity of learning. Through increasing creativity and productivity ofstudent learning, the absorptive capacity of students is also increasing. There were34 students (97 percent) who scored more than 70. It means that research targets have been achieved, even more, so that productive creative learning model issuccessful.Keywords:Creative productive learning model, Introductory Business,creativity and productivity of learning